Fiqh Lestari: ke arah penyusunan prinsip-prinsip muamalat islam untuk pembangunan lestari yang sepadu - Atikullah Abdullah, (Universiti Kebangsaan Malaysia, 2009)
There has been a general misunderstanding among Muslims and non-Muslims alike that Islamic fiqh only deals with aspects of worshipping and businesses (muamalat) that carry the name of Islam. This view holds that there is nothing that Islamic fiqh can contribute to other fields of human activities in order to ensure sustainable and harmonious life. Therefore, the aim of this article is to provide a counter argument and prove that Islamic fiqh encompasses all aspects of human life and able to contribute towards long lasting peaceful life. The author discusses how Islamic fiqh provides human beings with holistic guidelines towards a just and harmonious system of life